Bos primigenius in Ancient Egyptian art – historical evidence for the continuity of occurrence and ecology of an extinct key species - Carl Beierkuhnlein (Frontiers of Biogeography)
Knowledge of the habitat requirements and temporal stability of populations of extinct aurochs (Bos primigenius) is surprisingly scarce. Reliable reports of this species, which by its domestication remains tremendously important for humans, are rare. As the species became extinct about 400 years ago and regionally disappeared much earlier, its behaviour and morphology are also under debate. Aurochs is also a crucial component of the mega-herbivore theory in nature conservation, but in fact its natural habitat and behaviour are unknown. Here, I report records of aurochs for the time period of Ancient Egypt. They are found in archaeological sites and literature, and in collections. Records of the species continue through all the periods of Ancient Egypt. In particular, hunting scenes illustrating the merits of high-ranking persons, in their graves (mastabas) and temples, provide insights into the behaviour and ecology of the depicted game. Here, special attention is given to one outstanding hunting scene that is documented in a relief at the mortuary temple of Ramesses III (1175 BC, Medinet Habu, Egypt). Assisted by a group of hunters, the pharaoh kills three specimens of aurochs. The whole scene is stunningly realistic.  The adult specimen is fleeing towards the reed belt of the River Nile, suggesting that the species’ habitat was probably in large valley bottoms, where open grassland is regularly created by flooding. Endemic species of fish and game confirm that this scene took place in Lower Egypt. The regional populations of the North-African subspecies of aurochs probably went extinct shortly after this piece of art was produced. Records of species in ancient art can be very informative in terms of ecology and behaviour of species, especially when extinct species are addressed. In addition, the dating of old pieces of art containing biological information can be very precise, for instance when these refer to a historic personage.